1986
DOI: 10.1901/jaba.1986.19-397
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Low‐fat Entree Choices in a Public Cafeteria

Abstract: Reductions in dietary fat have been recommended in the prevention of coronary heart disease. Because entrees contribute substantially to total meal fat content, we evaluated a cafeteria-based intervention for increasing the purchase rate of low-fat entrees (M = 6.83 g) relative to nonlow-fat entrees (M = 25.59 g). The intervention included a poster listing the benefits of a LF diet and the daily LF entrees (i.e., broiled or baked chicken and fish dishes). During 6 days per phase, food selections (N = 3,264) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
4

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
0
15
0
4
Order By: Relevance
“…The majority of schemes in public eating places labelled healthy food choices ( Mayer et al , 1986 ; Albright et al , 1990 ; Green et al , 1993 ; Almanza, 1995). Albright's study was part of a long‐term community‐based CHD project (Stanford five city project).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of schemes in public eating places labelled healthy food choices ( Mayer et al , 1986 ; Albright et al , 1990 ; Green et al , 1993 ; Almanza, 1995). Albright's study was part of a long‐term community‐based CHD project (Stanford five city project).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies used a similar design: Mayer et al (1986 ) in the promotion of main courses, and Wagner & Winett (1988) for promoting salads. The studies included four consecutive phases of: baseline (no prompts)–intervention (promoting salads/main courses)–baseline (no prompts)–intervention (promoting salads/main courses).…”
Section: Introductionmentioning
confidence: 99%
“…One study used a single poster advertising the health benefits of the low-fat entree, which resulted in a 15% increase in purchases of that entree. 558 Wagner and Winett559 replicated these findings by successfully using signs and posters to cue healthful food choices in a fast food restaurant. They found that the cues for salads increased the sales of salads; sales of higher fat foods such as hamburgers and french fries did not decrease.…”
Section: Organization-level Interventionsmentioning
confidence: 90%
“…Dubbert et al (1984) used labelling and prompting strategies to increase sales of low-calorie items in cafeterias. Mayer et al (1986) used point-of-choice prompts and fliers in a public cafeteria to increase sales of low-fat entree choices. The Mayer et al (1986) intervention followed a number of guidelines for prompts (i.e., specify desirable, convenient behaviors using polite language, with the prompt in dose proximity to the target behavior; Geller, Winett, & Everett, 1982) and used pilot research for construction and placement of the prompts (Mayer, personal communication, October, 1986).…”
mentioning
confidence: 99%
“…The present study was a replication and extension of the study of Mayer et al (1986). Based on our own formative and pilot research, prompts were developed for a national chain fast-food restaurant.…”
mentioning
confidence: 99%